Ocorrência da cochonilha Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) em mudas de mogno (Swietenia macrophylla King) - de Castro, Marcelo Tavares; Montalvão, Sandro Coelho Linhares; Peronti, Ana Lúcia Benfatti Gonzalez; Monnerat, Rose Gomes (EntomoBrasilis, 2019)
Resumo. Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) é relatada pela primeira vez associada ao mogno brasileiro, Swietenia macrophylla King (Meliaceae). Infestações deste pseudococcídeo foram observadas sobre folhas e ramos de mudas do mogno cultivadas em casa de vegetação, em Brasília, Distrito Federal, Brasil. O controle da cochonilha foi realizado manualmente e/ou com aplicação de solução de água com detergente neutro a 10%. Occurrence of the mealybug Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) on mahogany seedlings (Swietenia macrophylla King) Abstract. Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) is reported for the first time on brazilian mahogany, Swietenia macrophylla King (Meliaceae). Infestations of this Pseudococcidae were observed on leafs and branches of mahogany seedlings cultivated in a greenhouse, in Brasilia, Federal District, Brazil. The control of the mealybug was realized manually and/or with application of water solution with 10% of neutral detergent.